Pentahelix Collaboration Concept as an Effort to Accelerate Poverty Reduction in the Covid-19 Situation in the City of Mataram - Inka Nusamuda Pratama; Adil Hassan Ibrahim; Paisal Akbar (Universitas Teuku Umar, 2023)
Pentahelix concept collaboration as an instrument to accelerate poverty alleviation in the Covid-19 situation in the City of Mataram. The Pentahelix concept is a form of the ability of elements (Government, Academics, Private, Community, Media) to build harmonious synergies in responding to accelerated poverty reduction amid the Covid-19 situation. The research method used is qualitative with a case study approach. Data collection techniques were carried out through interviews and documentation. The research results of the Pentahelix collaboration process (Government, Academics, Private, Community, Media) in poverty alleviation in the City of Mataram have been well established. This can be seen from the negotiations that took place between the government as a policymaker and other Pentahelix elements. Commitment from every element in Pentahelix in every poverty alleviation policy and program in the Covid-19 situation in the City of Mataram which was carried out as the implementation of a joint decision. the involvement of various actors such as the Government, Academics, Private, Community, and Media, especially in alleviating poverty in the City of Mataram due to the Covid-19 Pandemic is going well.